Optimization of Biogas Generation from Press Mud in Batch Reactor - Rouf, MA; Bajpai, PK; Jotshi, CK (Bangladesh Journal of Scientific and Industrial Research, 2011)
Press mud collected from sugar mills in Punjab, India were characterized and found to contain 75-80% organic matter, which mainly consists of cellulose, hemicellulose, lignin, protein, sugar, wax, etc. Biogas generation from press mud in a 2-litre batch reactor was studied at solid concentrations of 4 to 12%. Maximum yield of biogas was 0.24 L/g with 6% solids. Effect of Co++ and Ni++ concentrations on biogas yield was also studied. It was maximum at 5 μ moles/L of Co++ and 6 μ moles/L of Ni++. The optimum C/N ratio for biogas generation was 18, which was higher than the normal C/N ratio of 14 in the press mud. Other substrates such as cow dung, bagasse and cane pith when mixed with press mud in different proportions have influenced biogas generation. Press mud when mixed with cow dung, biomethanation process became more stable. Particularly, cane pith when mixed with press mud in 1:1 ratio, the generation of biogas increased significantly. The methane content of the biogas was about 65%. Key words: Anaerobic digestion; Press mud; Biogas DOI: 10.3329/bjsir.v45i4.7383 Bangladesh J. Sci. Ind. Res. 45(4), 371-376, 2010